Cultures of sustainability governance in higher education institutions: A multi‐case study of dimensions and implications. (16th December 2019) - Niedlich, Sebastian; Kummer, Benjamin; Bauer, Mara; Rieckmann, Marco; Bormann, Inka
Abstract: Organisational culture is frequently mentioned in the context of sustainability governance in higher education institutions, but its substance and role for organisational development remain largely unclear. This paper argues that, in fact, sustainability governance in higher education institutions is predicated on cultural orientations. These are explored empirically based on 61 expert interviews with stakeholders (management, sustainability commissioners, academic and technical staff, students) in eleven German higher education institutions. Qualitative (thematic, evaluative) content analysis was used to code and compare data across cases. The study identifies four cultural key dimensions and two overarching orientations: organisational learning orientation and holistic orientation. The analysis suggests that both orientations tend to reinforce each other. They also represent key areas which need to be addressed by higher education institutions seeking change towards sustainable development. The findings demonstrate the need for future research on organisational cultures of sustainability governance and their development over time. Zusammenfassung: Im Kontext der Governance von nachhaltiger Entwicklung an Hochschulen werden häufig Fragen organisationaler Kultur aufgeworfen; deren Wesen und Rolle für die Organisationsentwicklung von Hochschulen bleiben indes weitgehend unklar. Der Beitrag argumentiert, dass organisationskulturelle Merkmale eine wesentliche Grundlage für die Nachhaltigkeitsgovernance an Hochschulen darstellen. Dieser Annahme wird auf der Basis von 61 Experteninterviews mit verschiedenen Akteur*innen (Hochschulleitung, Nachhaltigkeitsbeauftragte, akademisches und technisches Personal, Studierende) in elf deutschen Hochschulen nachgegangen. Die Interviewdaten wurden im Rahmen einer strukturierenden und evaluativen qualitativen Inhaltsanalyse kodiert und vergleichend ausgewertet. Die Studie identifiziert vier zentrale Kulturdimensionen und zwei übergeordnete kulturelle Orientierungen: organisationale Lernorientierung sowie holistische Orientierung. Die Analyseergebnisse legen nahe, dass die beiden Orientierungen einander wechselseitig verstärken. Zugleich bilden sie zwei wichtige Gestaltungsbereiche für Hochschulen, die eine Transformation hin zu nachhaltiger Entwicklung anstreben. Insgesamt verdeutlichen die Ergebnisse die Notwendigkeit, hochschulische Organisationskulturen und deren Wandel genauer zu erforschen, um die Nachhaltigkeitsgovernance an Hochschulen besser verstehen und erklären zu können.